2017
DOI: 10.1111/1750-3841.13977
|View full text |Cite
|
Sign up to set email alerts
|

Fishy Odor and TMA Content Levels in Duck Egg Yolks

Abstract: The differences between the trimethylamine (TMA) content levels in duck and chicken egg yolks under normal dietary conditions were compared. Moreover, the association between the polymorphisms of the duck FMO3 gene and TMA content levels in duck egg yolks was analyzed. Then, to detect the mutations associated with the fish-flavor trait, duck populations were selected for a high-choline diet experiment, which was followed by full-length sequencing of the FMO3 exons. The results showed that the TMA content level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…The antibacterial properties of TMA also reflect the evolutionary adaptability of ducks to survival and reproduction. Previous studies have shown that the TMA content of duck and goose eggs is higher than that of chicken eggs [ 41 , 42 ]. Compared to the breeding environment of chickens, ducks and geese usually lay their eggs in wetter ponds or grasslands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial properties of TMA also reflect the evolutionary adaptability of ducks to survival and reproduction. Previous studies have shown that the TMA content of duck and goose eggs is higher than that of chicken eggs [ 41 , 42 ]. Compared to the breeding environment of chickens, ducks and geese usually lay their eggs in wetter ponds or grasslands.…”
Section: Resultsmentioning
confidence: 99%
“…We confirmed that the TMA concentration in egg yolks was sufficiently high to have antibacterial activity and that the TMA content increased with the extension of storage time. Previous studies have shown that the TMA content in egg yolks is significantly higher than that in egg whites [ 42 ]. Microorganisms were detected in the egg white, but no microorganisms were found in the yolk.…”
Section: Resultsmentioning
confidence: 99%
“…Laying hen diet containing 14% RSM increased TMA synthesis in the cecum and increased TMA deposition in yolk ( Long et al, 2017 ). It was reported that excessive TMA deposition in duck eggs was one of the main factors causing the fishy odor in duck eggs ( Li et al, 2018 ). It was speculated that the tolerance threshold of TMA levels in chick egg yolks for the human-perceived fishy odor is approximately 4 μg/g ( Ward et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Laying hen diets with high levels of RSM resulted in TMA metabolism load, thus inducing fishy odor eggs ( Ward et al, 2009 ; Long et al, 2017 ). TMA levels in duck eggs were significantly higher than those in chicken eggs under normal dietary conditions, and the excessive TMA deposition in duck eggs was one of the main factors causing the fishy odor in duck eggs ( Li et al, 2018 ). However, there was very little information about TMA deposition in duck eggs, and there was some doubt whether the inherent fishy smell of duck egg was induced by RSM.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with chicken eggs, duck eggs are richer in Omega-3 fatty acids and have high potential economic value ( Sinanoglou et al, 2011 ; Yang et al, 2020 ). However, in most cases, duck eggs have a stronger fishy odor than other poultry eggs, and are not preferred by consumers ( Li et al, 2017 ). Therefore, the fishy odor of duck eggs is the main limiting factor for their consumption and commercial development.…”
Section: Introductionmentioning
confidence: 99%